Gabriel Josipovici et la fabrique de l’ordinaire - Marcin Stawiarski (Revue LISA)
This paper focuses on the idea of the ordinary in the works of Gabriel Josipovici. It argues that the ordinary in Josipovici’s works is not only a theme, but is part and parcel of the writer’s novelistic strategies, characterising both language and narration. First, the paper centres on the way in which the ordinary is specifically conveyed through language. Second, it deals with the ordinary as a narrative technique. Third, the paper examines the phenomenon of quotidianisation, brought out by the representation of the ordinary. Finally, the article defines the overall conception of the ordinary as it appears in Josipovici’s works.